International Undergraduate Student Recruitment at China’s “Double First-Class” Universities - Li, Mei; Jiang, Qixia; Su, Shuli (Journal of International Students, 2022)
Focusing on the “Double First-class” universities in China, we analyze the recruitment policies of international undergraduate students at the institutional level. Findings indicate that “double First-class” universities have a certain autonomy in determining the recruitment scale and academic thresholds, demonstrating an unevenly set and loosely regulated policy decision making in China with an absence of a national academic standard and coordinative system. We categorize institutional policies at “double First-Class” universities into four kinds: Active-rigorous Player, Active Player, Rigorous Player and Inactive Player. As Active-rigorous Players, the most prestigious universities set admission requirements as strict as that of some research universities in North America. In general, academic rationale and economic rationale are not as important as political and social-cultural rationales in the recruitment policy. China’s HEIs need to maintain a subtle balance among academic, political, economic and social-cultural rationales, with more emphasis put on the quality control of international student recruitment.